2012
DOI: 10.1590/s0100-879x2012007500036
|View full text |Cite
|
Sign up to set email alerts
|

New perspective on the pathophysiology of panic: merging serotonin and opioids in the periaqueductal gray

Abstract: Panic disorder patients are vulnerable to recurrent panic attacks. Two neurochemical hypotheses have been proposed to explain this susceptibility. The first assumes that panic patients have deficient serotonergic inhibition of neurons localized in the dorsal periaqueductal gray matter of the midbrain that organize defensive reactions to cope with proximal threats and of sympathomotor control areas of the rostral ventrolateral medulla that generate most of the neurovegetative symptoms of the panic attack. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
1
16
0
2
Order By: Relevance
“…(12) Another study assumed that panic patients had defi cient serotonergic inhibition of neurons localized in the dorsal periaqueductal gray matter of the midbrain that organizes defensive reactions to cope with proximal threats and that the rostral ventrolateral medulla that generates most symptoms of the panic attack. (13) Other evidence has indicated that 5-HT 1A receptors in the dorsal periaqueductal gray matter and 5-HT 2A receptors in the dorsolateral septum mediate panic behavior in the elevated T-maze. (14,15) Additionally, copious evidence has demonstrated that the NE system also acts as a main role in the pathogenesis of panic attack.…”
Section: Discussionmentioning
confidence: 99%
“…(12) Another study assumed that panic patients had defi cient serotonergic inhibition of neurons localized in the dorsal periaqueductal gray matter of the midbrain that organizes defensive reactions to cope with proximal threats and that the rostral ventrolateral medulla that generates most symptoms of the panic attack. (13) Other evidence has indicated that 5-HT 1A receptors in the dorsal periaqueductal gray matter and 5-HT 2A receptors in the dorsolateral septum mediate panic behavior in the elevated T-maze. (14,15) Additionally, copious evidence has demonstrated that the NE system also acts as a main role in the pathogenesis of panic attack.…”
Section: Discussionmentioning
confidence: 99%
“…Moreira et al (2013) present a thoughtful review of the use of rodents in panic disorder research. Graeff (2012), studying an animal model of panic disorder found that the inhibitory action of serotonin is connected with activation of endogenous opioids in the periaqueductal gray (PAG). Schenberg and colleagues (Schimitel et al, 2012) suggest "[the PAG] harbors an anoxiasensitive suffocation alarm system".…”
Section: Panic and Comorbid Conditionsmentioning
confidence: 99%
“…Moreira et al (2013) present a thoughtful review of the use of rodents in panic disorder research. Graeff (2012), studying an animal model of panic disorder found that the inhibitory action of serotonin is connected with activation of endogenous opioids in the periaqueductal gray (PAG). Schenberg and colleagues (Schimitel et al, 2012) suggest “[the PAG] harbors an anoxia-sensitive suffocation alarm system”.…”
Section: Testing the Panic-suffocation-false Alarm-endogenous Opioid mentioning
confidence: 99%